PAI TEACHER STUDENTS' PERCEPTIONS ON THE IMPLEMENTATION OF ONLINE ASSESSMENT APPLICATIONS IN LEARNING - ningsih, yuni setia; Nurdin, Realita; Muslim, Buhori (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
In the digital era, Islamic Religious Education (PAI) teacher students are required to be familiar with forms of assessment in learning. The assessment can be done online via certain applications. One of the online assessment applications is Quizizz. The students who are potentially to improve the quality of education in the future must be able to understand the Quizizz online assessment application. They must be able to think critically by criticizing the advantages and disadvantages of the Quizizz application in learning assessment. This research aims to describe the perceptions of PAI teacher students regarding the implementation of the Quizizz application as an online assessment platform. This research was done in October 2023. To collect field data, researchers used a descriptive qualitative research design by using questionnaire. The questionnaire used is a Likert scale. The results of research on 44 PAI teacher students revealed that they tend to have very good perceptions on the implementation of the Quizizz application as an online assessment platform in learning. This is shown by the overall perception value of 85.15% in the very good category. Thus, it can be concluded that Quizizz as online assessment platform can be useful for teacher-candidate students and is possible to be applied in the future.